Long-Term Effects of Transcranial Direct-Current Stimulation in Chronic Post-Stroke Aphasia: A Pilot Study - Vestito, Lucilla; Rosellini, Sara; Mantero, Massimo; Bandini, Fabio (Frontiers in Human Neuroscience, 2014)
Transcranial direct current stimulation (tDCS) has been suggested to improve language function in patients with post-stroke aphasia. Most studies on aphasic patients, however, were conducted with a very limited follow-up period, if any. In this pilot, single-blind study on chronic post-stroke aphasic patients, we aimed to verify whether or not tDCS is able to extend its beneficial effects for a longer period of time (21 weeks after the end of stimulation). Three aphasic patients underwent anodal tDCS (A-tDCS, 20 min, 1.5 mA) and sham stimulation (S-tDCS) over the left frontal (perilesional) region, coupled with a simultaneous naming training (on-line tDCS). Ten consecutive sessions (five days per week for two weeks) were implemented. In the first five sessions we used a list of 40 figures, while in the subsequent five sessions we utilized a second set of 40 figures differing in word difficulty. At the end of the stimulation period we found a significant beneficial effect of A-tDCS (as compared to baseline and S-tDCS) in all our subjects, regardless of word difficulty, although with some inter-individual differences. In the follow-up period, the percentage of correct responses persisted significantly better until the 16th week, when an initial decline in naming performance was observed. Up to the 21st week, the number of correct responses, though no longer significant, was still above the baseline level. These results in a small group of aphasic patients suggest a long-term beneficial effect of on-line A-tDCS.